Strengthening Professionalism of School Principals Through Integrity, Communication Skills, and Teamwork - Sugiarto Sutomo; Masduki Ahmad; Matin Matin; Heni Rochimah (AL-ISHLAH: Jurnal Pendidikan, 2023)
In leading schools, principals often face ambiguity, changes in regulations, and challenges in learning. In dealing with these matters, the principal is required to always act professionally, so strengthening the principal's professionalism becomes important. There are many standards for the professionalism of school principals, including integrity, communication skills, and teamwork. The purpose of this study is to determine how integrity, communication skills, and teamwork affect the professionalism of Banten Province, Indonesia's school principals. This research is a quantitative study, with a sample of 122 school principals involved in Banten Province. The data were examined using multiple regression analysis, t-test, and F-test as hypothesis testing. The research results obtained are: i) Integrity has a positive and significant impact on strengthening the professionalism of school principals; ii) Communication skill has a positive and significant impact on strengthening the professionalism of school principals; iii) Teamwork has a positive and significant impact on strengthening the professionalism of school principals; iv) Integrity, communication skills, and teamwork simultaneously have a positive and significant effect on strengthening the professionalism of school principals by 62.1%. Based on these results, it is hoped that schools, supervisors, and the education office, especially Banten province, will pay attention and routinely carry out programs to strengthen the professionalism of school principals which include discussions on integrity, communication skills, and teamwork.